(untitled) (Research, Society and Development, 2021)
Brucellosis is one of the most important and neglected zoonotic diseases. Thus, the objective of this work was to describe the epidemiology, economic losses, and risk factors for brucellosis in bovine cattle, horses, dogs, and humans in the municipality of Flor do Sertão, state of Santa Catarina, Brazil. Exams for Brucella abortus were conducted from 2017 to 2018 in 2,750 bovines from 131 farms, 20 horses, and 29 dogs. Serological screening tests were used, followed by confirmatory tests (AAT and 2ME/SAT). Regarding the cases of brucellosis in humans, the municipality’s health department provided 206 serological results that were recorded in the same period of the study of cattle brucellosis. The prevalence of the disease for the populations was calculated and the decision tree test was applied using the Weka® statistical program to establish an association between risk factors and the positivity in the herds. The Spearman test (GraphPad Prism‑) was used to establish a correlation between brucellosis cases in humans and in bovine cattle. The tests encompassed 45.5% of the cattle population in the municipality, showing a prevalence of brucellosis of 0.29%. The annual economic losses were R (BRL) 14,747.92. The percentage of humans that tested positive for brucellosis was 5.33%. The factors associated with positivity for the disease were based on the consumption of dairy products without heat treatment, and prevalence of brucellosis above zero. The prevalence of brucellosis in bovine cattle in Flor do Sertão is low, but high for local outbreaks. However, the prevalence of the disease in humans was high, which were higher than the prevalence in animals, probably due to the risk factors associated with the positivity of the disease, such as the consumption of raw dairy products.